Prijevoz za potrebe gradnje objekta - Badanjak, Stjepan (Promet - Traffic&Transportation, 2012)
Timely delivery of material and equipment to the site at minimum costs and minimum risk makes one of the major elements in successful construction trade. Cutting down the time of equipment being ready for transport and the time of being actually delved on to the construction site can be attained through good preparations and sensible management. Transport program makes part of the complex process of construction of buildings connecting the manufacturing and construction program by making optimum use of the available time to grant timely flow of materials and equipment to the construction site at intervals and in quantities as defined in the construction/erection program. Experience shows that the preparation of a transportation program should be initiated as early as the time of the elaboration of the preliminary design. Being its integral part, the transport study considers in a professional and sensible way the usability of access lanes to the site, available transportation leans, development of the network of traffic links, construct of new ports, etc. The study gives an advance insight to concerned parties into the conditions of transport and conditions to be met by equipment for transport thus making possible timely preparation and management. By promoting successful transport it certainly adds to successful construction activities.